Just give money to the poor : the development revolution from the global south - Hanlon, Joseph; Barrientos, Armando; Hulme, David (Kumarian Press, 2010)
* Argues strongly for overlooked approach to development by showing how the poor use money in ways that confound stereotypical notions of aid and handouts* Team authored by foremost scholars in the development fieldAmid all the complicated economic theories about the causes and solutions to poverty, one idea is so basic it seems radical: just give money to the poor. Despite its skeptics, researchers have found again and again that cash transfers given to significant portions of the population transform the lives of recipients. Countries from Mexico to South Africa to Indonesia are giving money.